Effect of Preconditioning with Desflurane on Phosphorylated Glycogen Synthase Kinase 3β Contents in an Experiment - V. V. Likhvantsev; O. A. Grebenchikov; R. A. Cherpakov; Yu. V. Skripkin; K. Yu. Borisov (Общая реаниматология)
The purpose of this study is to determine and evaluate if the preconditioning with desflurane depends on level of phosphoGSK3β.Material and methods. White outbred male rats (56) were randomly allocated to 6 groups. Ischemia/reperfusion modeling was performed using V. G.Korpachev's technique. The reference group consisted of sham (falselyoperated) animals. The second group underwent global ischemia/reperfusion after anesthesia with chloral hydrate. The next two groups were treated with either sevoflurane or desflurane at 1 MAC. In the final two groups, the use of same anes thetics was followed by global ischemia/reperfusion. The concentration of phosphoGSK3β in brain homogenate was determined using western blotting. A statistical analysis was performed using the MannWhitney Utest, and the difference was considered significant at P<0.05. A threeminute ischemia with subsequent reperfusion resulted in a significant increase in the concentration of phosphoGSK3β vs. the reference group (620437 relative units vs. 304574 relative units, respectively, P<0.05). Similar results were observed in groups where animals received inhaled sevoflurane (743166 relative units) and desflurane (667119 relative units) alone (P<0.05). In the ischemia/reperfusion group, the concentration of phosphoGSK3β was equal to 922231 relative units after inhalation of sevoflurane (P<0.05 vs. the reference group). In the group with a combination of desflurane and ischemia/reperfusion, the enzyme concentration increased up to 677084 relative units (P<0.05 vs. reference group). No difference in concentrations of the enzyme between groups receiving inhaled anesthetics with and without ischemia/perfusion was found. In addition, the concentration of this enzyme was comparable with that in the ischemia/reperfusion group. Conclusion. Two anesthetics under testing possess similarly increased concentration of phosphoGSK3β in rat brain homogenates.